Determinan Kepemilikan Jaminan Kecelakaan Kerja pada Pekerja Informal di Provinsi Jawa Timur - Hery Wahyu; Lia Yuliana (Inferensi, 2022)
The informal sector is often seen as workers with low wages, difficult and dangerous jobs, and low protection. The high rate of work accidents makes the importance of work accident insurance for all workers, especially informal workers. Work Accident Insurance is a benefit in the form of cash and health services provided when a participant experiences a work accident or illness caused by the work environment. This study aims to determine the factors that influence Occupational Accident Benefit ownership for informal sector workers in East Java Province in 2021 using the binary logistic regression method. The data used comes from August 2021 SAKERNAS data. The results of this study show that the variables of the area of residence, gender, income, age, marital status, education, and the number of household members affect Occupational Accident Benefit ownership status. Informal sector workers who have a greater tendency to have Occupational Accident Insurance are informal workers with the characteristics of residing in urban areas, male gender, having income greater than or equal to the provincial minimum wage, have been married, having an age range of 15- 25 years old, minimum education is high school, and the maximum number of household members is 4 people